Win at All Costs or Lose Gracefully in High-Stakes Competition? Gender Differences in Professional Tennis. (May 2016) - Anbarci, Nejat; Lee, Jungmin; Ulker, Aydogan
This article examines line-call challenges by male and female professional tennis players in major tournaments around the world. In terms of utilization rates, we find that the genders behave similarly. Nevertheless, we do detect some intriguing gender differences in these challenges. First, male players' challenges are more likely to be provoked by those of their opponents. More importantly, at tiebreaks, females are more likely to reverse an umpire's unfavorable call, while males make relatively more unsuccessful challenges. Furthermore, we find that men are a lot more likely to make "embarrassing" line-call challenges at tiebreaks and offenses (i.e., when the shot lands at the opponent's side of the tennis court) than women. These significant gender differences suggest that women particularly diverge from men at crucial junctures of the match such as tiebreaks. Differences in factors such as risk aversion, overconfidence, pride, shame, and strategic signalling behavior might help us to explain these gender-difference findings in line call challenges.